Workup of lacrimal drainage disorders - Linberg, John V.; Tucker, Susan M.; Tucker, Nancy A.; American Academy of Ophthalmology (San Francisco : American Academy of Ophthalmology, 1994)
Offers a systematic, step-by-step approach to evaluating the lacrimal out-flow system in patients with tearing, which is useful in determining the cause of epiphora. Demonstrates external examination, dye disappearance test, and irrigation and probing of the lacrimal system. Shows the nasal exam using rigid endoscopy. Introduces an instrument that measures lacrimal resistance as it applies to the evaluation of obstructions. Illustrates dacryocystography, CT and MRI.
John V. Linberg, Susan M. Tucker, Nancy A. Tucker
Keywords: Lacrimal Apparatus Diseases -- diagnosis; Lacrimal Apparatus Diseases -- surgery; Dacryocystorhinostomy -- methods